2015
DOI: 10.1371/journal.pone.0129402
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Lysosomal Membrane Protein, GLMP, in Mice Results in Metabolic Dysregulation in Liver

Abstract: Ablation of glycosylated lysosomal membrane protein (GLMP, formerly known as NCU-G1) has been shown to cause chronic liver injury which progresses into liver fibrosis in mice. Both lysosomal dysfunction and chronic liver injury can cause metabolic dysregulation. Glmpgt/gt mice (formerly known as Ncu-g1gt/gtmice) were studied between 3 weeks and 9 months of age. Body weight gain and feed efficiency of Glmpgt/gt mice were comparable to wild type siblings, only at the age of 9 months the Glmpgt/gt siblings had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 65 publications
(80 reference statements)
1
18
0
Order By: Relevance
“…In wild-type mice Glmp expression increased rapidly after birth, coinciding with the rapid growth of both liver and the animal. In a recent report, we showed that the liver/body weight ratio more than doubled in the first 2 weeks of life [ 39 ]. In the early phase of life, the liver metabolism has to adapt to lactation and in this scenario, the lack of GLMP presumably causes the chronic liver injury leading to the observed fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In wild-type mice Glmp expression increased rapidly after birth, coinciding with the rapid growth of both liver and the animal. In a recent report, we showed that the liver/body weight ratio more than doubled in the first 2 weeks of life [ 39 ]. In the early phase of life, the liver metabolism has to adapt to lactation and in this scenario, the lack of GLMP presumably causes the chronic liver injury leading to the observed fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Nelson et al [ 56 ] showed that iron deposition specifically in Kupffer cells was associated with metabolic liver injury. In a recent study, we have demonstrated dysregulation of glucose and lipid metabolism in Glmp gt/gt liver and isolated primary hepatocytes [ 39 ]. The absence of signs of liver injury in newborn Glmp gt/gt mice suggests that GLMP may not be essential in mouse prenatal life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C3H1orf85 encodes glycosylated lysosomal membrane protein and was also known as GLMP . Data indicated that increased flux of glucose, increased de novo lipogenesis and lipid accumulation were detected in lysosomal protein NCU-G1 ( GLMP ) gt/gt primary hepatocytes[72]. Compared with the wild-type myotubes, myotubes from GLMP (gt/gt) mice metabolized glucose faster and had a larger pool of intracellular glycogen, while oleic acid uptake, storage and oxidation were significantly reduced [73].…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing revealed homozygous variants in four candidate genes including, GLMP , SYNPO2 , FGG and TBCD (Additional file 1 : Table S2). GLMP encodes glycosylated lysosomal membrane protein which has role in the metabolic regulation of liver [ 15 ]. We excluded this variant since the patient did not have any liver disease.…”
Section: Discussionmentioning
confidence: 99%